Teething: Misconceptions and Unhealthy Practices among Residents of a Rural Community in Nigeria (2017)
Misconceptions about the teething process has led to high infant morbidity and mortality, which was recently experienced in Nigeria due to consumption of an adulterated drug used in the prevention and treatment of teething-related illnesses in infants. It is however, unknown if these misconceptions still persist in a rural town in Nigeria despite oral health awareness campaigns targeted at this. The aim of this study is to assess the beliefs and practices of residents in Igbo Ora, a rural township in Nigeria, regarding the teething process. A descriptive cross-sectional study was conducted among 393 adults in Igbo Ora using a 33-item, semistructured questionnaire. Symptoms such as diarrhea (80.7%), fever (69.2%), and boils (64.4%) were still considered as a must to accompany teething. Teething powder, teething syrup, and traditional concoctions were commonly recommended by (42.0%), (31.6%), and (48.1%) of the respondents, respectively, to treat and prevent teething symptoms. This study revealed that misconceptions about teething are still highly prevalent among the populace in Igbo Ora, and a structured oral health education intervention at the community level is urgently needed